The 3D printing technology and its application in Nepalese context - Chaulagain, Raj Kumar (Journal of Innovations in Engineering Education, 2021)
3DP has become popular on manufacturing platform that enables users to create customizable products through digital design. In context of 3DP's application in developing countries, Nepal is at an early stage. This paper presents a brief review of 3DP technology and case study conducted through survey on application of 3DP in Nepalese environment. The research showed presently professional and research based organization holds higher coverage among 40 different organizations spread over seven districts of the country. Though the technology is in use since 2011, it was found increasing from 2015 only. Product examples of 3DP application in Nepal were found more concerned to medical consumables and student project components. The findings of research are discussed plotting different graphs and moreover concluded with brief opportunity and challenges of using 3DP in Nepal.